Influence of Elevation on Growth Performance and Root Traits of 2-Year-Old Terminalia copelandii in Sukau, Kinabatangan, Sabah - Khatta, Aida Nabihah M; Nanak, Ag Syahmil Qyusairi Ag; Dumil, Haverdly; Thabet, Thamer Abdulrahman; Wakimin, Nur Fadzlunnisaa’; Kelvin, Pang Kat Nyen; Chen, Si; Terhem, Razak; Hassan, Affendy (Jurnal Sylva Lestari, 2026)
Terminalia copelandii is a native, fast-growing tree with potential for forest restoration and agroforestry in Sabah. There is a limited understanding of the effects of elevation on the growth and below-ground root strategies of smallholder farms. This paper examines growth patterns and underground structure of two-year-old T. copelandii grown at different altitudes in Sukau, Kinabatangan, Sabah. Tree height (TH) and diameter at breast height (DBH) were measured at a hilly site and a lowland site. A completely randomized design with three experimental units per site was used. Root traits assessed included specific root length (SRL), root length density (RLD), and root biomass (RB). Roots were extracted at soil depths of 25 cm, 75 cm, 125 cm, and 175 cm and analyzed using an independent t-test at a 5% significance level. Results showed significantly better growth at the lowland site (TH: 4.77 m; DBH: 12.58 cm) than the hilly site (TH: 1.87 m; DBH: 6.48 cm). SRL and RLD were similar at shallow depths but increased at 175 cm in the lowland site. The hilly site showed greater root biomass accumulation, although the difference was not statistically significant. These results demonstrate how elevation-induced environmental factors affect above-ground and below-ground performance, promoting forest restoration and agroforestry strategies for this valuable species. Keywords: fast growing species, forest plantation, root biomass, root phenotyping, Terminalia copelandii